Sistemática dos gêneros Alphamenes Van der Vecht, 1977 e Minixi Giordani Soika, 1978 (Hymenoptera, Vespidae, Eumeninae) - Oliveira, Letícia Aparecida de (2017)
Studies with the subfamily Eumeninae, have been expanded in the last years, mainly with phylogenetic studies, investigating the relationship between species of some genera, taxonomic revision works and descriptions of new species. However, the taxonomy and relationship of many Eumeninae lineages still remain unclear. In this sense, a study is needed to investigate the phylogeny of the genera Minixi Giordani Soika, 1978 and Alphamenes Van der Vecht, 1977, which will bring important contributions to a phylogenetic classification for the subfamily. The main goal of this work was to perform a systematic study of the two genera mentioned above, using cladistic methods and morphological data; to test the monophyly of the genera and to carry out necessary taxonomic procedures. The methodology used was to examine the external morphology of dry preserved specimens borrowed from collections of museums and institutions from Brazil and abroad, and male genitalia. Later, the construction of an array of characters and cladistic analyses were carried out. All recognized species of Alphamenes and Minixi were included as an internal group. Relatively related species belonging to the genus Pachymenes de Saussure, 1852 were also included. For the rooting of the tree Monobia angulosa de Saussure, 1852 was used as external group. Heuristic searches for the most parsimonious cladograms were performed using the implicit weighing of the characters and the support for the branches was estimated by symmetrical re-sampling. Alphamenes and Minixi were recovered as monophyletic groups, corroborating previous hypotheses with fewer species. Three large clades were analyzed for the species of the genus, with the following phylogenetic relationships: ((Pachymenes + Alphamenes) + Minixi)). Internal relations within the two genera were elucidated and almost fully resolved. However, there is still a need for more in-depth studies, especially regarding the relationships between Minixi lineages. The delimitation of females for the genus Alphamenes is imprecise and confusing, due to the morphological homogeneity presented among species. In this sense, another important point of this work was the delimitation of some females of Alphamenes: A. campanulatus, A. usitatus and A. insignis. Two males of Minixi are described for the first time. In addition, it is proposed in this work an identification key for the species of Alphamenes, with the inclusion of females, and the synonymizat ion of a subspecies of Alphamenes.